2014
DOI: 10.1039/c3cc47942k
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite chemistry derived from nitric oxide reaction with a Cu(ii)–OOH species and a copper mediated NO reductive coupling reaction

Abstract: New peroxynitrite-copper chemistry ensues via addition of nitric oxide (•NO(g)) to a CuII-hydroperoxo species. In characterizing the system, the ligand-Cu(I) complex was shown to effect •NO(g) reductive coupling, a new reaction type. Biological implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Beckman 2b,c,g and Koppeno 2c have discussed this in particular for the interaction of PN with the enzyme CuZn-superoxide dismutase or Fe III -EDTA (or other) coordination complexes and postulate that metal ions favor heterolytic cleavage of the PN O−O bond to give nitronium ion (NO 2 + ), which is a powerful nitrating agent. More recently, Girault 12f has shown that copper ion complexes may mediate PN formation and then phenol nitration. Metal-bound PN complexes have now been shown by other groups 12a,c,e,f,41 to react with substituted phenols, in particular 2,4-di- tert -butylphenol (DTBP) as an analytically useful substrate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Beckman 2b,c,g and Koppeno 2c have discussed this in particular for the interaction of PN with the enzyme CuZn-superoxide dismutase or Fe III -EDTA (or other) coordination complexes and postulate that metal ions favor heterolytic cleavage of the PN O−O bond to give nitronium ion (NO 2 + ), which is a powerful nitrating agent. More recently, Girault 12f has shown that copper ion complexes may mediate PN formation and then phenol nitration. Metal-bound PN complexes have now been shown by other groups 12a,c,e,f,41 to react with substituted phenols, in particular 2,4-di- tert -butylphenol (DTBP) as an analytically useful substrate.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Girault 12f has shown that copper ion complexes may mediate PN formation and then phenol nitration. Metal-bound PN complexes have now been shown by other groups 12a,c,e,f,41 to react with substituted phenols, in particular 2,4-di- tert -butylphenol (DTBP) as an analytically useful substrate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations